Asymmetric HIV-1 co-receptor use and replication in CD4(+) T lymphocytes - Mariani, Samanta A (BioMed Central, 2011)
Susceptibility to infection by the human immunodeficiency virus type-1 (HIV-1), both in vitro and in vivo, requires the interaction between its envelope (Env) glycoprotein gp120 Env and the primary receptor (R), CD4, and Co-R, either CCR5 or CXCR4, members of the chemokine receptor family. CCR5-dependent (R5) viruses are responsible for both inter-individual transmission and for sustaining the viral pandemics, while CXCR4-using viruses, usually dualtropic R5X4, emerge in ca. 50% of individuals only in the late, immunologically suppressed stage of disease. The hypothesis that such a major biological asymmetry is explained exclusively by the availability of cells expressing CCR5 or CXCR4 is challenged by several evidences. In this regard, binding of the HIV-1 gp120 Env to the entry R complex, i.e. CD4 and a chemokine R, leads to two major events: virion-cell membrane fusion and a cascade of cell signaling. While the fusion/entry process has been well defined, the role of R/Co-R signaling in the HIV-1 life cycle has been less characterized. Indeed, depending on the cellular model studied, the capacity of HIV-1 to trigger a flow of events favoring either its own latency or replication remains a debated issue. In this article, we will review the major findings related to the role of HIV R/Co-R signaling in the steps following viral entry and leading to viral spreading in CD4(+) T lymphocytes.